ADMINISTRATIVE-LEGAL REGULATION OF ANTI-MONEY LAUNDERING DURING MARTIAL LAW IN UKRAINE - Holota, Nataliia (Sworld-Us Conference proceedings, 2025)
This study examines the primary challenges of anti-money laundering (AML) systems during armed conflicts, utilizing Ukraine’s experience following the Russian invasion on February 24, 2022, as a case study. It demonstrates that traditional AML mechanisms,